INTERSECTIONALITY, DOCUMENTATION AND VIOLENCE - Lemos Igreja, Rebecca; Dias Rampin, Talita Tatiana; Sierra Camacho, Maria Teresa; de Carvalho Dantas, Fernando Antônio; Cevallos, Sofia (Universidade de Brasília, 2021)
Editorial of the first issue of the fifth volume of the magazine "Abya Yala -Journal on access to justice and rights in the Americas".